Using Spreadsheet Modeling in Basic Physics Laboratory Practice for Physics Education Curriculum - Fauzi, Ahmad; Rahardjo, Dwi Teguh; Romadhon, Utoro; Kawuri, Kunthi Ratna (International Journal of Science and Applied Science: Conference Series, 2018)
Physics is one of a branch of science which uses much of mathematical concept. Usually, the concept of physics is expressed in a mathematical equation; it will make physics easier to be understood. Therefore, the students need to understand about mathematical modelling to help them understand physics. Students who take fundamental physics and physics laboratory course required to understand the concept of feedback that is mathematically expressed in differential equations. However, most of the students have not been taught the concept of differential equations at early semester. Therefore, we are interested in reviewing the use of mathematical modelling with a spreadsheet in the case of feedback that is integrated with laboratory practice. The results of this study indicate that students gave positive perceptions and improve their ability in understanding the concept of feedback that is mathematically expressed in the differential equation.